Pengaruh Penambahan Abu Sekam Padi Terhadap Kekuatan Tekan Dan Porositas Genteng Tanah Liat Kabupaten Pringsewu - Kusuma, Mei Indra; Tarkono, .; Badaruddin, Moh. (FT UNILA, 2013)
Rice’ husk ash’ prosperous in silica (siO2). Silica in construction term, especially concrete technology had already been used as additional ingredient. Husk ash is used as additional ingredient of clay roof tile making process. It is made by compounding of clay, sand, water andhusk ash. Then, they are mashed by extruder machine and forming of kuweh and then, airing for three days before the process of stamping. The roof tile is dried for four days then there is fumigation for twelve days and continued by combustion for also twelve days. The examination which used is press and porosity examination with the aim of knowing whether there is additional impact of rice’ husk ash’ existence or not into clay roof tile in Kabupaten Pringsewu. Theresearch’s results showed that there is conversion of press and porosity power compared with roof tile without rice’s husk ash composition. The optimum value for the press and porosity examination is obtained from the roof tile with 5% rice’s husk ash’ composition with the press power’s average value 11.118 KPa and the porosity average value 20.16%. The minimum value for the press and porosity power is obtained from the roof tile without rice’s husk ash’s composition with the press power’s average value 8.393 KPa and its porosity average value 21.92%.Keywords: clay roof tile, rice husk ash, silica (SiO2), press power, porosity.